The Influence of Organizational Commitment and Training on Employee Performance at Perum Bulog Makassar with Job Satisfaction as an Intervening Variable - WULANDARI, Monica Rizki; JIMAD, Habibullah; RIBHAN, Ribhan (PT Keberlanjutan Strategis Indonesia, 2023)
The purpose of this study was to determine the effect of organizational commitment on employee performance. job training on employee performance. organizational commitment on job satisfaction. training on job satisfaction. and job satisfaction mediates between organizational commitment on employee performance. job satisfaction also mediates training on employee performance . This study used the SEM-Amos analysis tool. the research was carried out in a quantitative study with a sample size of 240 with a sideways purposive method. The empirical findings obtained are where organizational commitment is positive and significant on employee performance. training is positive and significant on employee performance. organizational commitment is positive and significant on job satisfaction. training is positive and significant on job satisfaction. the influence of organizational commitment on employee performance indirectly directly mediated by job satisfaction which is positive and significant. the effect of training on employee performance through job satisfaction is positive and significant.